Mechanical and Physical Properties of Glass-Fiber Reinforced Polymer Rods Manufactured by Different Pultrusion Methods - Hossein Alikhani; Fatemeh Sharifzadeh; Hadi Khoramishad (Mechanics of Advanced Composite Structures)
In this study, different methods of pultrusion including the out-of-mold and in-mold ultraviolet (UV)-cured and thermal pultrusion methods were investigated by comparing the mechanical and physical properties of the manufactured glass fiber-reinforced composite rods. The experimental results showed that the specimens fabricated by the UV-based methods were cured more uniformly and six times faster compared to the specimens made by thermal pultrusion. However, the specimens fabricated using the out-of-mold methods had higher diameter expansion and void content due to the lack of mold pressure during the curing process. Moreover, the mechanical responses of the specimens manufactured by different pultrusion methods were compared by conducting quasi-static tensile and low-velocity Charpy impact tests. The quasi-static tensile and Charpy impact strengths of the in-mold UV-cured specimens were 15.2% and 34.8% higher than those of the out-of-mold UV-cured specimens and 6.7% and 7.4% higher than those of the thermal-cured specimens, respectively. Furthermore, the fracture surfaces of the specimens were analyzed using SEM photography.